2017
DOI: 10.1002/hbm.23739
|View full text |Cite
|
Sign up to set email alerts
|

Associations between self‐reported sleep quality and white matter in community‐dwelling older adults: A prospective cohort study

Abstract: Both sleep disturbances and decline in white matter microstructure are commonly observed in ageing populations, as well as in age‐related psychiatric and neurological illnesses. A relationship between sleep and white matter microstructure may underlie such relationships, but few imaging studies have directly examined this hypothesis. In a study of 448 community‐dwelling members of the Whitehall II Imaging Sub‐Study aged between 60 and 82 years (90 female, mean age 69.2 ± 5.1 years), we used the magnetic resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
98
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(110 citation statements)
references
References 41 publications
7
98
5
Order By: Relevance
“…The lateralization is not explained by handedness, as we ran the NBS analysis with handedness as co-variate and found the same results. In contrast to our findings, two previous studies reported insomnia-related reductions in white-matter integrity that were largely right-lateralized Sexton et al, 2017). However, left hemisphere alterations in relation to insomnia symptoms have also been reported previously, including reduced volume of the left orbitofrontal cortex (Altena et al, 2010) and of the area bordering the left insula and orbitofrontal cortex (Stoffers et al, 2012).…”
Section: Left Hemisphere Lateralizationcontrasting
confidence: 99%
See 1 more Smart Citation
“…The lateralization is not explained by handedness, as we ran the NBS analysis with handedness as co-variate and found the same results. In contrast to our findings, two previous studies reported insomnia-related reductions in white-matter integrity that were largely right-lateralized Sexton et al, 2017). However, left hemisphere alterations in relation to insomnia symptoms have also been reported previously, including reduced volume of the left orbitofrontal cortex (Altena et al, 2010) and of the area bordering the left insula and orbitofrontal cortex (Stoffers et al, 2012).…”
Section: Left Hemisphere Lateralizationcontrasting
confidence: 99%
“…Kang and colleagues specifically investigated the neural connectivity of the left thalamus and inferior frontal gyrus, and found that patients with insomnia had reduced fractional anisotropy and axial diffusivity in the tract connecting these two regions (Kang et al, 2018). Furthermore, disturbances of fronto-subcortical white-matter integrity were also found to be related to poor sleep quality in a large study with community-dwelling older adults (Sexton et al, 2017). A recent DTI study assessed topological alterations in Insomnia Disorder, and found changes of the regional organization of frontal and subcortical areas as well as reduced connectivity in frontal networks (Wu et al, 2018).…”
mentioning
confidence: 99%
“…Both measures decreased in association with poor sleep (Amorim et al, ). In related work, a structural MRI study carried out in 448 community‐dwelling older adults showed that poor sleep quality was associated with reduced global FA and increased global axial and radial diffusivity values of frontal white matter tracts (Sexton et al, ), thus suggesting that sleep quality is linked to white matter microstructure. However, the direction of any causal relationship between the two remains to be elucidated.…”
Section: Sleep and Myelinmentioning
confidence: 99%
“…On the other hand, diffusion tensor imaging studies have shown decreased fractional anisotropy (which denotes microstructural integrity loss) in several white matter tracts in patients with insomnia and community-dwelling individuals with self-reported poor sleep quality [11,22,23].…”
Section: Introductionmentioning
confidence: 99%